Raising dairy heifers: a business - J.L. Morrill (Kansas Agricultural Experiment Station Research Reports, 1994)
On many dairy farms, improvement is needed in raising replacement heifers, especially in providing proper nutrition and management to allow for freshening at 23 to 24 mo of age at a desirable size. With larger herds, there is a trend toward more specialization, which may (but may not) result in more attention to, or responsibility for, proper care and management of the heifer. In some cases, the heifers are raised by a person at a location away from the dairy farm on which they originated, and contract raising of dairy replacements has several potential advantages and disadvantages. These are discussed in this paper, along with the results that should be expected and some of the types of programs and typical charges when heifers are raised on contract.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; Heifers; Contract raising; Growth